Defined Daily Dose and Cost of Therapy of Empirical Ceftriaxone Pre- and Post-Antimicrobial Stewardship Program Model Implementation in Sepsis Patients in A Tertiary Hospital in Indonesia - Uun Sumardi; Anggra Filani; Evan Susandi; Ida Parwati (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: Antibiotic resistance requires substantial responses through two mechanisms: new antibiotic development and smart antibiotic use. Antibiotic Stewardship Program (ASP) is one of the responses that reduce the overall antibiotics use and prevent the overuse of antibiotics to avoid antibiotic resistance. The purpose of this study was to assess the difference in defined daily dose (DDD) and the cost of therapy (COT) for empirical ceftriaxone therapy in sepsis patients pre- and post-ASP model implementation in Dr. Hasan Sadikin General Hospital, Bandung.Methods: A pre- and post-intervention quasi-experimental study on ASP model implementation in empirical ceftriaxone therapy provided to sepsis patients treated in the intensive or semi-intensive care units was performed from December 2015 to July 2016 using the Mann Whitney test and t-test. The DDD was calculated as DDD/100 patient-days, while the COT was calculated as the COT/patient-day. The ASP model intervention implemented in these units applied 2 main strategies: ceftriaxone use restriction and ceftriaxone therapy duration audit.Results: Participants of this study consisted of 112 sepsis subjects (n=112) with 55 subjects in the pre-ASP group and 57 subjects in the post-ASP group. The mean DDD/100 patient-days in the post-ASP subject was lower than that of the pre-ASP (16.3±4.3 and 45.8±16.8; p=0.018). The median COT/patient-days in post-ASP subject was IDR 42,000 (IDR 14.000–42.000), which was lower than that of the pre-ASP group of IDR 84.000 (IDR 28.000–420.000, p=0.001).Conclusion: The differences in the DDD/100 patient-day and COT/patient-day values between the pre-ASP and post-ASP are significant. The ASP model applied in Dr. Hasan Sadikin General Hospital, Bandung leads to a smart use of ceftriaxone and reduces costs for the empiric ceftriaxone therapy in sepsis patients.